A Simulation Framework for Performance Analysis of Molecular Nano Communication Networks - Shams, Behzad Amirzadeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Nanonetworks have attracted a lot of attention over the past decade due to advances in nanotechnology and their wide range of biomedical, industrial, environmental, and military applications. Nanodevices are made up of nanoscale components and are capable of performing only simple computation, sensing, and actuation tasks. A nanonetwork is formed when nanodevices are interconnected. In a nanonetwork, nanodevices can cooperate and share information to achieve more complex tasks. Nanomachines can employ diffusion-based molecular communication as a possible, biocompatible information transport method. Unlike traditional communication techniques in which electromagnetic waves are employed as information carriers, molecules are considered as carrier signals to convey the information. For instance, a transmitter nanomachine encodes the message symbols into the molecular signals and then sends them into a fluidic propagation channel. These information molecules propagate in the medium according to Fick’s laws of diffusion, and then are received by the receiver nanomachine at which the information is decoded. In this work, a simulation framework for molecular nano communication networks will be developed. In particular, transmission, propagation channel, and the reception processes of molecules will be analyzed. The simulator will then be used to analyze specific performance metrics in a diffusion-based molecular communication network. The simulator will also provide a three-dimensional visualization of the network. Keywords: Nanonetworks, Molecular Communication, Diffusion, Simulation

ÖZ: Nano-ağlar son yıllarda, nanoteknolojideki ilerlemeler ve biyomedikal, endüstriyel, çevresel ve askeri alanlardaki geniş uygulamalarından dolayı dikkat çekmiştir. Nano-ölçekte bileşenleri olan nano-aygıtlar, kendi başlarına sadece basit işlemler, algılamalar ve eyleyim yapabilirler. Nano-ağlar, nano-aygıtların birbiriyle bağlanmasıyla oluşur. Nano-ağlarda, nano-aygıtlar daha karmaşık işlemler için işbirliği ve bilgi paylaşımı yapabilirler. Nanomakineler arasında iletişim için kullanılan metodlardan biri biyo-uyumlu moleküllerin difüzyonudur. Bu metod, elektromagnetik dalgaların kullanıldığı alışılmış iletişim tekniklerinin aksine, bilgi taşıyıcı olarak molekülleri kullanır. Gönderici bir nanomakine, bilgiyi moleküllere kodlayıp sıvı bir ortama bırakır. Moleküller Fick kanununa göre yayılıp bir alıcı nanomakine tarafından alınır. Bu çalışmada, nano iletişim ağları için bir benzetim çerçevesi geliştirilmiştir. Özellikle, moleküllerin iletim, yayılım ve alış süreçleri analiz edilmiştir. Benzetici ile difüzyona dayalı moleküler iletişimin performans ölçütleri değerlendirilmiştir. Benzetici ayrıca, nano-ağın üç boyutlu görselleştirmesinde de kullanılabilmektedir. Anahtar kelimeler: Nano-ağlar, Moleküler iletişim, Difüzyon, Benzetim
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Assoc. Prof. Dr. Doğu Arifler.
Keywords: Computer Engineering; Wireless communication systems; Wireless Technology - Computer Communication Networks; Nanonetworks; Molecular Communication; Diffusion; Simulation